Organizational antecedents and capabilities and their effects on firm competitiveness of sustainable supply chain management: An empirical evaluation in a developing economy (2017)
Drawing from the Resource-Based View and Stakeholder theories, this article aims to evaluate empirically the relationship between organizational antecedents, firm capabilities for Sustainable Supply Chain Management (SSCM), and the latter’s effects on competitive advantage for a group of 126 focal firms in the city of Bogotá, Colombia. A mixed methods research design was followed. A self-administered (online) questionnaire was sent to a convenience sample of firms. The validity and reliability of the theoretical constructs were verified through validated factors modeled using reflective indicators, and the structural equation model was tested using partial least squares (PLS). Along with internal consistency, convergent and discriminant validities of the measurement model were evaluated. Finally, the constructs of organizational antecedents, SSCM practices and their effects on the focal company’s competitive advantage appear to be properly in line with the data collected and the testing of the proposed framework has provided an acceptable fit with positive relationships between the factors involved.